The Hong Kong Region 1850-1911 : Institutions and Leadership in Town and Countryside - Hayes, James, 1930- (Book collections on Project MUSE., 2012)
The Hong Kong Region, now being reprinted by Hong Kong University Press in its "Echoes" series, was a historical reconstruction of certain long-settled villages and sub-districts in the New Territories of Hong Kong, and, more specifically, an enquiry into the nature of local society in the late Qing period, 1850-1911. Since the book was published in 1977, and much new material has appeared in print in the intervening thirty-four years, a new Introduction is called for. It will describe the favorable circumstances in which I came to research its contents, re-state the book's main propositions, review them in the light of the scholarly studies which bear on these topics, and update and carry them forward with the assistance of other authors and through my own later research and publications.